PENGARUH PERKOTAAN TERHADAP DRIVING BEHAVIOR BERDASARKAN FAKTOR USIA - Angela Claudia; Jeane Leony; Victoria C. Bijanto (MANASA, 2018)
This research is to seek out the effect of urbanized cities on driving behaviors of people with age factor as its comparison medium. The initial behavior of a person comes from within themselves, their past experiences and including the people surrounding them. The objective is to look at how circumstances that cause a disturbance in traffic flow affected driving behaviors of people of different ages excluding a third factor which is individual personality. We have used a method of quantitative analysis to obtain data required for this research. Our quantitative analysis is in the form of a questionnaire which we spread out randomly and is answered by people with the age criteria that we have stated. We hypothesized that the younger a person is the more that they are prone to break a traffic rule due to lack of driving experience and their likeliest to disposed the same behavior of a person breaking a traffic rule. The results has shown that past experience is not a determinant of how good a person’s driving behavior are even of different age. Nonetheless, it’s the thinking process of 2 age groups that determines their decision making in driving. Moreover, their responsiveness towards traffic situation is different in both age groups and the cause can be seen through their driving accidents.